2007
DOI: 10.2174/156800907780809714
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet B Regulation of Transcription Factor Families: Roles of Nuclear Factor-kappa B (NF-κB) and Activator Protein-1 (AP-1) in UVB-Induced Skin Carcinogenesis

Abstract: Prolonged and repeated exposure of the skin to ultraviolet light (UV) leads not only to aging of the skin but also increases the incidence of non-melanoma skin cancer (NMSC). Damage of cells induced by ultraviolet B (UVB) light both at the DNA level and molecular level initiates the activation of transcription factor pathways, which in turn regulate the expression of a number of genes termed the "UV response genes". Two such transcription factor families that are activated in this way are those of the nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
137
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(144 citation statements)
references
References 111 publications
4
137
0
Order By: Relevance
“…We also found that N ‐acetyl cysteine (NAC, a ROS scavenger) drastically inhibited sUV‐induced matrix metalloprotein‐1 (MMP‐1) expression (data not shown) and siRNA of p47 phox , a subunit of NADPH oxidase (NOX); as a result, reduction of EGFR transactivation in NADPH oxidase was observed (Chen et al., 2006). ROS also mediates UV‐induced skin inflammation via activation of inflammatory signaling pathways (Choi et al., 2016; Cooper & Bowden, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…We also found that N ‐acetyl cysteine (NAC, a ROS scavenger) drastically inhibited sUV‐induced matrix metalloprotein‐1 (MMP‐1) expression (data not shown) and siRNA of p47 phox , a subunit of NADPH oxidase (NOX); as a result, reduction of EGFR transactivation in NADPH oxidase was observed (Chen et al., 2006). ROS also mediates UV‐induced skin inflammation via activation of inflammatory signaling pathways (Choi et al., 2016; Cooper & Bowden, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…It seems that curcumin and curcuminoids mediate their therapeutic effects by modulating NF-kB target genes. Resveratrol inhibited TPA stimulated activation of AP-1 in mouse skin in vivo and, applied topically, attenuated NF-kB activation by blocking IKK activity (Cooper & Bowden, 2007). Curcumin also, suppressed the TNF-dependent activation of IKK and as a result it inhibited the translocation of the p65 subunit.…”
Section: Apoptotic Regulatorsmentioning
confidence: 93%
“…Ultraviolet irradiation of cultured human dermal fibroblasts (HDFs) in vitro or human skin in vivo induces the production of reactive oxygen species (ROS) and MMPs (3). UVB irradiation can induce MMP expression by activating transcription factors such as NF-jB and AP-1 (4) through the MAPK signalling pathway (4).…”
Section: Introductionmentioning
confidence: 99%